La descentralización fiscal y el desarrollo sostenible a nivel mundial. - Dorado Nuñez, Angel Darío (2025)
This study investigates the impact of fiscal decentralization on sustainable development in 41 countries over a period of 30 years (1990–2019). The research methodology uses a panel data econometric model to analyze how different dimensions of fiscal decentralization, specifically revenue decentralization and expenditure decentralization of subnational governments, influence sustainable development outcomes. The analysis is controlled by key factors such as government efficiency, dependence on natural resources, energy consumption patterns, and demographic changes. The study shows a main contrast: revenue decentralization has positive and statistically significant effects, while expenditure decentralization has negative impacts.